Reconfiguration of the Banking Intermediation Model in the Era of Digital Disruption: A Modern Financial Economics Perspective - Rukiah; Riny Viri Insy Sinaga; Erpiana Siregar (Yayasan Darussalam Bengkulu, 2026)
Background: Background: Digital transformation has driven fundamental changes in the banking intermediation model, moving from a conventional, institution-based system to a more open and integrated digital financial ecosystem. The emergence of financial technology, big data, artificial intelligence, and blockchain has shifted the traditional role of banking toward platform-based models, raising important questions about how intermediation functions are being reconfigured and what implications this holds for the financial system. Method: This study employs a qualitative approach with a descriptive-analytical design using library research. Data were collected through documentation studies and systematic literature reviews of scientific journals, industry reports, and policy documents from the Financial Services Authority (OJK) and Bank Indonesia. Data analysis was conducted using interactive qualitative analysis techniques including data reduction, data presentation, and conclusion drawing, supported by thematic and conceptual comparative analysis. Results: The findings reveal a shift from bank-based intermediation to platform-based intermediation, where banks are transforming into orchestrators in the digital financial ecosystem through the integration of open banking and embedded finance concepts. Four driving factors were identified: technological development, changing customer behavior, fintech emergence, and regulatory policies. This transformation improves operational efficiency and financial inclusion but also presents new risks such as cyber risk, regulatory complexity, and potential systemic risk. Conclusion: The reconfiguration of banking intermediation represents a paradigm shift from centralized institution-based systems to hybrid network-based financial ecosystems. Adaptive strategies from banks and responsive policies from regulators are essential to balance innovation with financial system stability.